2021
DOI: 10.1055/s-0041-1735587
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis of Transanal Endoscopic Microsurgery versus Total Mesorectal Excision in the Treatment of Rectal Cancer

Abstract: Background Transanal endoscopic microsurgery (TEMS) has been suggested as an alternative to total mesorectal excision (TME) in the treatment of early rectal cancers. The extended role of TEMS for higher stage rectal cancers after neoadjuvant therapy is also experimented. The aim of this meta-analysis was to compare the oncological outcomes and report on the evidence-based clinical supremacy of either technique. Methods Medline, Embase, and Cochrane databases were searched for the randomized controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…A recent metaanalysis compared only TME to TEM surgical procedures for the outcome (local recurrence) and found only three RCTs for inclusion. They reported that there was no difference between the two interventions as regards to local recurrence or postoperative complications [ 29 ]. In our metaanalysis we included two of the three RCTs but unfortunately we didn’t find the full manuscript of Chen et al [ 30 ] to extract the data from, so it was not included on our final analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent metaanalysis compared only TME to TEM surgical procedures for the outcome (local recurrence) and found only three RCTs for inclusion. They reported that there was no difference between the two interventions as regards to local recurrence or postoperative complications [ 29 ]. In our metaanalysis we included two of the three RCTs but unfortunately we didn’t find the full manuscript of Chen et al [ 30 ] to extract the data from, so it was not included on our final analysis.…”
Section: Discussionmentioning
confidence: 99%
“…With widespread neoadjuvant treatment use, 15–27 % of patients achieve a pathological complete response (pCR), and 60–70 % reach tumour downstaging after neoadjuvant treatment [24] , [25] , [26] . Following neoadjuvant treatment, TEM may play an extended role in carefully selected patients with LARC for active surveillance [8] , [9] . Rutger et al .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a high local recurrence rate limits TEM application to LARC patients [6] . Neoadjuvant treatment induces tumour downstaging and reduces local recurrence risk, which is expected to expand TEM use to patients with advanced LARC [7] , [8] , [9] . Patients with a complete or “near” complete response to neoadjuvant treatment followed by TEM could achieve good oncological outcomes and improved quality of life [7] , [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Also, one-third had to undergo radical surgery ( 36 ). A 2021 metanalysis of randomized controlled trials of TEMS vs. radical surgery concludes that in T1N0 patients may be offered TEMS, but in locally advanced cases radical surgery remains the mainstay ( 37 ).…”
Section: Discussionmentioning
confidence: 99%